Antiaromatic Cyclooctatetraene-Embedded, BODIPY-Fused Nanographene with an NIR-II Chiroptical Response - Ziying Liu; Xiuxiu Yang; Wentao Hou; Zixin Liu; Yinjun Xie; Ze-Hua Wu; Yanwei Gu (Journal of the American Chemical Society, 2026)
Abstract Chiral nanographenes exhibiting near-infrared (NIR) chiroptical responses are of growing interest due to their potential applications in bioimaging, sensing, and photodetectors. Nevertheless, realizing the chiroptical response in the NIR-II region (1000–1700 nm) remains a fundamental challenge. Herein, a BODIPY-fused anthracene (BNG1) and an unprecedented BODIPY-fused nanographene (BNG2) incorporating a cyclooctatetraene (COT) unit are synthesized. Single-crystal X-ray crystallography confirms their structures, revealing that BNG2 adopts an enantiomeric double-helical architecture. The embedded COT unit possesses a pronounced antiaromatic character, as supported by multiple theoretical analyses. Both compounds display strong absorption spanning the UV–visible–NIR regions, especially the π-extended BNG2, which shows broad absorption with a long tail reaching 1800 nm in toluene solution, attributed to the antiaromaticity and low C2-symmetry of COT. BNG1 and BNG2 have narrow optical energy gaps of 1.32 and 0.90 eV, H-aggregation behaviors, and excellent photothermal stability. Most importantly, enantiomers of BNG2 are successfully resolved by chiral high-performance liquid chromatography and exhibit mirror-image circular dichroism spectra with opposite Cotton effects extending from the UV region to the NIR-II region. This implies its potential applications in the detectors of wide-range circularly polarized light and chirality-based phototherapy. Our investigation provides important insights into developing purely organic materials with robust NIR chiroptical responses.